1480 A description of the effectiveness of screening overseas workers for latent tb. (24th April 2018) - Kelly, S; Reid, A; Noone, P
Abstract : Introduction: Healthcare workers(HCW) are at increased risk of aquiring Tuberculosis (TB) than the general population. In Ireland a pre-employment screen for TB is recommended for all clinical staff working with patients or clinical specimens. Those workers arriving from countries with annual TB rates >40 per 1 00 000 population are classified as high priority HCW. Screening involves: Questionnaire, Tuberulin skin test (TST) or Interferon Gamma Release Assay (IGRA) testing, and Chest x–ray. The aim of our study was to estimate the prevalence of latent TB in these high priority HCW and their screening outcomes and follow up. Methods: A retrospective study was carried out on all high priority HCW screened for latent TB between January 2014 and December 2016 across two multicentre occupational health services. We recorded numbers screened, results of TST/IGRA testing, outcome of clinical review and follow up attendance. Results: 505 high priority HCW were screened over 3 years. 17% (87/505) tested positive for latent TB. Of the 74 reviewed at clinic to date, 26% (19/74) completed treatment and 74% (55/74) declined treatment or defaulted from follow up. Number Needed to Screen(NNS) was calculated as 333 based on estimates of a 10% lifetime risk of reactivation and 70% relative risk reduction after 6 months of treatment with Isoniazid. 1 Discussion: Of the 17% of high priority HCW who tested positive for Latent TB, an unexpectedly high proportion (75%) declined treatment or did not attend for follow up. The NNS for similar populations varies widely in the literature, but our number of 333 although high, is within the range reported. 2 These results raise questions over the cost-effectiveness and proportionality of the current screening process as a method of preventing TB among HCWs and protecting patients from forward transmission.